Tick- and flea-borne rickettsioses in Tizi-Ouzou, Algeria: Implications for travel medicine. Issue 26 (November 2018) - Bouchaib, Hayet; Eldin, Carole; Laroche, Maureen; Raoult, Didier; Parola, Philippe
Abstract: Background: In Algeria, Mediterranean spotted fever (MSF), caused by Rickettsia conorii conorii and transmitted by Rhipicephalus sanguineus ticks, is endemic. However, the documentation of cases is rare due to a lack of laboratory facilities. Our aim was to screen for rickettsioses in patients with fever, rash and a possible inoculation eschar. Materials and methods: Between 2013 and 2015, patients with a fever and a rash presenting at hospitals in the Tizi-Ouzou region were prospectively included in our study. Sera were screened using Indirect Immunofluorescence Assay (IFA) and qPCR was performed on swab samples from eschars. Results: One hundred and sixty-six patients were included. For 57 patients, MSF due to R. conorii conorii was diagnosed by serology and qPCR on a swab eschar sample. Three patients were diagnosed with murine typhus, a flea borne rickettsiosis. In addition, two patients had a positive serology in IgM for R. felis . For nine patients, serology for rickettsiosis was positive, but the specific rickettsia involved could not be determined. Nine patients had a severe disease with neurological involvement or multi-organ failure. Conclusion: Clinicians should routinely screen for rickettsioses in patients and travellers presenting with a rash upon return from Algeria. Doxycycline treatment must be given promptly because the prognosis can be severe.